Trauma and Violent Misconduct Among Incarcerated Juveniles: the Mediating Role of Mental Health - Craig, Jessica M. (Journal of developmental and life-course criminology, 2023)
Though most research focuses on antisocial behavior that occurs outside of correctional institutions, it is also important to understand the etiology of such behavior that occurs inside a correctional institution, generally referred to as institutional misconduct. Most misconduct studies have relied upon the importation model, finding evidence that factors that predict violence outside an institution also predict violence inside an institution. Two such risk factors include poor mental health and childhood trauma exposure. However, researchers have yet to consider the potential mediating pathways between these variables and misconduct. The current study sought to address this gap and examined if poor mental health mediates the impact of trauma exposure on violent misconduct among a sample of institutionalized juvenile delinquents. Data from a large southern state found evidence of a partial mediation effect, suggesting trauma-exposed youth were more likely to experience mental health problems which, in turn, increased their likelihood of engaging in violent misconduct. Results also revealed a significant direct relationship between trauma exposure and violent misconduct. A discussion of these findings is presented, along with their policy implications.